Legal Regulations of Public Performance Contract to Protect Jordanian Author's Copyrights and the Related Rights. - Abu Baker, Mohammad Khalil Yousif (Journal of Human Security (Librello Publishing House), 2025)
The study undertook a detailed examination of the legal regime applicable to public performance contracts, with particular attention to their legal nature, governing rules, and essential components in order to determine the corresponding rights and duties of the parties involved. It further explored the legal outcomes associated with such contracts, including the effects of termination, the importance of confining the agreement to a specified time frame, and the necessity of executing it in written form. The research followed a descriptive-analytical method, whereby relevant statutory provisions and recognised legal sources were critically assessed to develop a more accurate interpretation of the applicable legal framework. The findings demonstrate a notable deficiency within the Jordanian legislative system. The Jordanian legislator has not established dedicated legal provisions to regulate public performance contracts in line with their particular characteristics. Instead, the current approach depends on general principles of contract law, which are inadequate for addressing the intricate legal and economic aspects of this contemporary contractual structure. This lack of specific regulation gives rise to uncertainty in relation to the definition of rights, the extent of contractual obligations, and the procedures governing dispute resolution. The study ultimately asserts that comprehensive legislative reform is essential to achieve legal certainty, ensure adequate protection for authors and performers, and reinforce the cultural and economic significance of public performance contracts.